2021
DOI: 10.3390/land10060586
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater-Extracting Rice Production in the Rejoso Watershed (Indonesia) Reducing Urban Water Availability: Characterisation and Intervention Priorities

Abstract: Production landscapes depend on, but also affect, ecosystem services. In the Rejoso watershed (East Java, Indonesia), uncontrolled groundwater use for paddies reduces flow of lowland pressure-driven artesian springs that supply drinking water to urban stakeholders. Analysis of the water balance suggested that the decline by about 30% in spring discharge in the past decades is attributed for 47 and 53%, respectively, to upland degradation and lowland groundwater abstraction. Consequently, current spring restora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
11
0
3
Order By: Relevance
“…The Generic River Flow (GenRiver) Model (van Noordwijk et al, 2017b) is a distributed process-based model that transforms plot-level water balances to landscape scale. Beyond the estimates for water transmission, buffering peak flow and infiltration (W1 – W3A) of the current model version (https://www.worldagroforestry.org/output/genriver-generic-river-model-river-flow), an updated version (β-tested) has groundwater parameters to accommodate the functions W3B and W3C (Khasanah et al, 2021). Further steps link flow persistence F p and overland flow to slope/riparian stability (W5) and soil erosion/sedimentation (W6).…”
Section: Proposed Mimetrics For Human Impacts On Water Cyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Generic River Flow (GenRiver) Model (van Noordwijk et al, 2017b) is a distributed process-based model that transforms plot-level water balances to landscape scale. Beyond the estimates for water transmission, buffering peak flow and infiltration (W1 – W3A) of the current model version (https://www.worldagroforestry.org/output/genriver-generic-river-model-river-flow), an updated version (β-tested) has groundwater parameters to accommodate the functions W3B and W3C (Khasanah et al, 2021). Further steps link flow persistence F p and overland flow to slope/riparian stability (W5) and soil erosion/sedimentation (W6).…”
Section: Proposed Mimetrics For Human Impacts On Water Cyclesmentioning
confidence: 99%
“…Groundwater over-use in lowlands is the main reason artesian spring discharge declines in the Rejoso watershed in Indonesia (Khasanah et al, 2021). Tree cover as a predictor of infiltration with thresholds differing between elevation zones on a single mountain (Suprayogo et al, 2020) leads to an optimal intermediate tree density phenomenon, similar to what was described for the Sahelian zone (Ilstedt et al, 2016; van Noordwijk et al, 2019).…”
Section: Application In a Set Of Tropical Watershedsmentioning
confidence: 99%
“…Groundwater-extracting rice production in the Rejoso watershed (Indonesia) reducing urban water availability: characterization and intervention priorities [7] Rice production using ground-water from AF hillslopes…”
Section: Comparing Land Use Systemsmentioning
confidence: 99%
“…The tree canopy characteristics required for infiltration-friendly land use clearly varied over short distances with soil type and rainfall intensity showing that generic rules, such as a 30% forest cover requirement, cannot be the basis for local resource management using agroforestry concepts. A study of the water balance and the impacts of lowland water use in the same watershed through uncontrolled flow of Artesian wells found that equal attention is needed for the upstream and downstream parts of the watershed if urban water supply is to be secured [7].…”
Section: Water Balance Effects Of Lowland Water Usementioning
confidence: 99%
“…Groundwater-extracting rice production in the Rejoso watershed (Indonesia) reducing urban water availability: characterization and intervention priorities [7] Rice production using ground-water from AF hillslopes Water balance effects of lowland water use…”
Section: Comparing Land Use Systemsmentioning
confidence: 99%